1.1-sinα cosα (1-sinα)(1+sinα) -cos²α 1-sin²α-cos²α
-------- - --------- = ------------------------------ = -------------------- =
cosα 1+sinα cosα(1+sinα)
cosα(1+sinα)
cos²α-cos²α 0
---------------- =---------------------- =0
cosα(1+sinα)
cosα(1+sinα) cosα
2.tg(3π/2-α)·sin(π-α)+cos(π+α)=ctgα·sinα-cosα= -------- ·sinα-cosα=
sinα
=cosα-cosα=0
1 1
cos²α+ ---------------- cos²α + ----------------
1+ctg²α 1/sin²α
3.---------------------------------------- =----------------------------------------- =
tgα tgα
cos²α+sin²α 1
---------------- =--------- = ctgα
tgα tgα